The science and technology of kinematic measurements in a century of Journal of Experimental Biology - McHenry, M. J.; Hedrick, T. L. (The Journal of Experimental Biology, 2023)
Kinematic measurements have been essential to the study of comparative biomechanics and offer insight into relationships between technological development and scientific progress. Here, we review the 100 year history of kinematic measurements in Journal of Experimental Biology (JEB) through eras that used film, analog video and digital video, and approaches that have circumvented the use of image capture. This history originated with the career of Sir James Gray and has since evolved over the generations of investigators that have followed. Although some JEB studies have featured technological developments that were ahead of their time, the vast majority of research adopted equipment that was broadly available through the consumer or industrial markets. We found that across eras, an emphasis on high-speed phenomena outpaced the growth of the number of articles published by JEB and the size of datasets increased significantly. Despite these advances, the number of species studied within individual reports has not differed significantly over time. Therefore, we find that advances in technology have helped to enable a growth in the number of JEB studies that have included kinematic measurements, contributed to an emphasis on high-speed phenomena, and yielded biomechanical studies that are more data rich, but are no more comparative now than in previous decades.